2011
DOI: 10.1037/a0020378
|View full text |Cite
|
Sign up to set email alerts
|

Implicit sequence learning and contextual cueing do not compete for central cognitive resources.

Abstract: Sequence learning and contextual cueing explore different forms of implicit learning, arising from practice with a structured serial task, or with a search task with informative contexts. We assess whether these two learning effects arise simultaneously when both remain implicit. Experiments 1 and 2 confirm that a cueing effect can be observed under a continuous setting and that there is no interference between contextual cueing and sequence learning. Experiments 3a and 3b tested whether an interference arises… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 52 publications
1
24
0
Order By: Relevance
“…Many contextual cuing studies have used post-experiment tests to gauge explicit knowledge of the relationship between target position and distractor configuration, typically using one of two measures: recognition of the repeated contexts indexed by "old" vs. "new" judgments of repeated and novel configurations (Chun & Jiang, 1998) or generation tasks where the participant must judge where the target should be located within a given configuration of distractors (Chun & Jiang, 2003). These two measures have yielded similar results, with many studies either failing to find evidence of better recognition for repeated configurations (Chun & Jiang, 1998;Chun & Phelps, 2001;Howard, Dennis, Howard, Yankovich, & Vaidya, 2004;Manns & Squire, 2001;Rausei, Makovski, & Jiang, 2007) or finding generation performance equivalent to chance (Chun & Jiang, 2003;Jiménez & Vázquez, 2010), despite the presence of robust contextual cuing effects. In some studies where these posttest measures have detected some degree of explicit knowledge (performance above chance), contextual cuing still appears to be unaffected by the participant's level of awareness, and cuing effects have been observed reliably in subgroups of participants who show no explicit recognition (Preston & Gabrieli, 2008;Vaidya, Huger, Howard, & Howard, 2007).…”
Section: Contextual Cuingmentioning
confidence: 52%
“…Many contextual cuing studies have used post-experiment tests to gauge explicit knowledge of the relationship between target position and distractor configuration, typically using one of two measures: recognition of the repeated contexts indexed by "old" vs. "new" judgments of repeated and novel configurations (Chun & Jiang, 1998) or generation tasks where the participant must judge where the target should be located within a given configuration of distractors (Chun & Jiang, 2003). These two measures have yielded similar results, with many studies either failing to find evidence of better recognition for repeated configurations (Chun & Jiang, 1998;Chun & Phelps, 2001;Howard, Dennis, Howard, Yankovich, & Vaidya, 2004;Manns & Squire, 2001;Rausei, Makovski, & Jiang, 2007) or finding generation performance equivalent to chance (Chun & Jiang, 2003;Jiménez & Vázquez, 2010), despite the presence of robust contextual cuing effects. In some studies where these posttest measures have detected some degree of explicit knowledge (performance above chance), contextual cuing still appears to be unaffected by the participant's level of awareness, and cuing effects have been observed reliably in subgroups of participants who show no explicit recognition (Preston & Gabrieli, 2008;Vaidya, Huger, Howard, & Howard, 2007).…”
Section: Contextual Cuingmentioning
confidence: 52%
“…These two awareness tests have produced similar results; many studies either failed to find evidence of better recognition for repeated configurations (Chun & Jiang, 1998;Chun & Phelps, 1999;Colagiuri, Livesey, & Harris, 2011;Howard, Howard, Dennis, Yankovich, & Vaidya, 2004;Manns & Squire, 2001;Rausei, Makovski, & Jiang, 2007) or found generation performance equivalent to chance (Chun & Jiang, 2003;Jimenez & Vazquez, 2011), despite clear evidence of contextual cuing effects. Even in studies that have detected some degree of knowledge of the repeated configurations, that is performance above chance, contextual cuing appears unaffected by the participant's level of awareness, with cuing effects reliably observed in sub-groups of participants who show no explicit awareness (Preston & Gabrieli, 2008;Smyth & Shanks, 2008 Experiment 2, but not Experiment 1; Vaidya, Huger, Howard, & Howard, 2007).…”
Section: Introductionmentioning
confidence: 53%
“…A continuous version of the CC task was used, in which successive trials followed each other with minimal delay (50 ms) and were not preceded by a fixation point. Jiménez and Vázquez (2009) have shown that this procedure results in levels of learning similar to the usual discrete version developed by Chun and Jiang (1998). In addition, Jiménez and Vázquez's (2009) procedure was followed by using four different responses instead of the usual twoalternative task.…”
Section: Apparatusmentioning
confidence: 97%